Regulation potential of earthworms as related to diversity and functioning of soil microbial community - Koubová, Anna (Jihočeská univerzita, 2016)
Earthworm-microbial interactions with emphasis on the passage effects of Eisenia spp. on microbial community were investigated. The study was focused on earthworm potential to regulate functional microbiota in cattle-impacted soils. Microbial communities were studied through a combination of polar lipid analyses, molecular, and culturing methods.
Regulation potential of earthworms as related to diversity and functioning of soil microbial community
Keywords: Earthworms; soil; microbial community; archaea; bacteria; Eisenia fetida; Eisenia andrei; gut passage; anaerobes; methanogens; outdoor husbandry; pasture soil.; Earthworms; soil; microbial community; archaea; bacteria; Eisenia fetida; Eisenia andrei; gut passage; anaerobes; methanogens; outdoor husbandry; pasture soil.